2014
DOI: 10.1007/s12022-014-9346-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PAX6 and PAX8 as Immunohistochemical Markers for Pancreatic Neuroendocrine Tumors

Abstract: To compare the utility of PAX6 and PAX8 as immunohistochemical markers for neuroendocrine tumors (NETs) of pancreatic origin, we performed PAX6 and PAX8 immunostains on 178 NETs, including 110 primary NETs (26 pancreatic, 10 gastric, 12 duodenal, 22 jejuno-ileal, 10 rectal, 30 pulmonary) and 68 NETs metastatic to the liver (24 pancreatic, 1 duodenal, 37 jejuno-ileal, 1 rectal, 5 pulmonary). Among primary NETs, PAX6 and PAX8 were positive in 65 % (17/26) and 73 % (19/26) of pancreatic, 0 % (0/10) and 10 % (1/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…The latter included markers commonly used in surgical pathology practice to demonstrate an origin from epithelia of the breast (gross cystic disease fluid protein‐15 (GCDFP‐15), estrogen receptor (ER)), Müllerian system (paired box 8 (PAX‐8), ER), lung (Napsin A, thyroid transcription factor‐1 (TTF‐1)), kidney (PAX‐8, Napsin A), liver (hepatocyte paraffin 1 (HepPar1)), salivary gland (GCDFP‐15), and thyroid (PAX‐8, TTF‐1) . As 100% of pituitary adenomas are immunoreactive for synaptophysin and chromogranin, the analysis also included TTF‐1, which may be positive in both pulmonary and extrapulmonary neuroendocrine carcinomas, as well as PAX‐8, which has been reported in a subset of metastatic neuroendocrine tumors . The spectrum of immunoreactivities for each of these markers was examined in 40 pituitary adenomas, sub‐classified by available clinical data and immunophenotype.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The latter included markers commonly used in surgical pathology practice to demonstrate an origin from epithelia of the breast (gross cystic disease fluid protein‐15 (GCDFP‐15), estrogen receptor (ER)), Müllerian system (paired box 8 (PAX‐8), ER), lung (Napsin A, thyroid transcription factor‐1 (TTF‐1)), kidney (PAX‐8, Napsin A), liver (hepatocyte paraffin 1 (HepPar1)), salivary gland (GCDFP‐15), and thyroid (PAX‐8, TTF‐1) . As 100% of pituitary adenomas are immunoreactive for synaptophysin and chromogranin, the analysis also included TTF‐1, which may be positive in both pulmonary and extrapulmonary neuroendocrine carcinomas, as well as PAX‐8, which has been reported in a subset of metastatic neuroendocrine tumors . The spectrum of immunoreactivities for each of these markers was examined in 40 pituitary adenomas, sub‐classified by available clinical data and immunophenotype.…”
Section: Introductioncontrasting
confidence: 68%
“…12 As 100% of pituitary adenomas are immunoreactive for synaptophysin and chromogranin, 10 the analysis also included TTF-1, which may be positive in both pulmonary and extrapulmonary neuroendocrine carcinomas, 18,19 as well as PAX-8, which has been reported in a subset of metastatic neuroendocrine tumors. 20 The spectrum of immunoreactivities for each of these markers was examined in 40 pituitary adenomas, subclassified by available clinical data and immunophenotype.…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, a panel of site-specific lineage markers (TTF-1 for pulmonary origin, CDX2 for gastrointestinal tract origin, PAX8/PAX6 for gastropancreatic and duodenal origin, and ER/PR, mammaglobin, GCDFP-15 and GATA3 for mammary origin) may be helpful in distinguishing metastatic neuroendocrine neoplasms (particularly well-differentiated neuroendocrine tumors) from invasive mammary carcinomas with neuroendocrine differentiation. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] In this study, CDX2 was positive in all examined metastatic neuroendocrine neoplasms of small bowel origin, TTF-1 was positive in 70% of examined metastatic neuroendocrine neoplasms of lung origin, and ER and GATA3 were positive in 91 and 100% of invasive mammary carcinomas with neuroendocrine differentiation, respectively. Similarly, in the study by Perry et al 9 (which with the exception of one high-grade neuroendocrine carcinoma consisted entirely of well-differentiated neuroendocrine tumors), all metastatic neuroendocrine neoplasms from the gastrointestinal tract expressed CDX2 and 60% of tumors originating from the lung expressed TTF-1.…”
Section: Discussionmentioning
confidence: 81%
“…232 Therefore, polyclonal antibodies should be used if PAX8 is included in the workup panel and monoclonal anti-PAX8 antibodies will not work. In fact, Lai et al 231 have shown similarly high detection rates for pancreatic, duodenal and rectal NETs when a monoclonal anti-PAX6 antibody is used.…”
Section: Grading Neuroendocrine Neoplasms By Ki-67mentioning
confidence: 93%
“…223,224,[229][230][231] It is positive in 7% to 22% of gastric, appendiceal, and colonic NETs, and has been consistently negative in jejunoileal NETs. The reported frequency of positivity in pulmonary NETs ranges from 0% to 23%.…”
Section: Grading Neuroendocrine Neoplasms By Ki-67mentioning
confidence: 99%